Pedagogical Knowledge Competencies Among Students/Teachers in the Mathematics Department and Their Relationship to Professional Motivation - misanjas, misanjas; Hamel Hussei , Duha; Abdel Zahra Alwan, Haider ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The research aims to identify the level of pedagogical knowledge competencies. of students/teachers in the Mathematics Department and their relationship with their professional motivation. The researchers followed a correlational descriptive survey method, and a simple random sample of (40) male and female students from the Mathematics Department was selected. The researchers prepared an observation card in the areas of (planning - implementation - classroom management - evaluation) to measure pedagogical knowledge competencies, as well as scales for professional motivation. The necessary psychometric properties for both were verified. The results showed that students do not possess the necessary pedagogical knowledge competencies for teaching, but they have a high motivation towards the teaching profession, and the relationship between pedagogical knowledge competencies and professional motivation was weak.